Investigating Sediment Grain Size Distribution and Transport Patterns in Punatsangchhu River, Punakha, Bhutan - Tenzin, Sangay; Dorji, Ugyen (CV. Literasi Indonesia, 2025)
This study investigates bed load sediment transport dynamics in selected areas of Punatsangchhu River, focusing on rock type identification, their association with topography, grain size distribution, and factors influencing bed load transport rates. 1D numerical sediment transport modeling was also done in HEC-RAS 6.3.1 using the discharge data of four years from 2020 to 2023. Bed load sediment samples were collected from 55 plots laid systematically 500 meters apart along the river. Results reveal Granite as the predominant rock type, reflecting the region's geological complexity shaped by Himalayan tectonics. Significant associations between rock types and topography, particularly for Granite Boulder, highlight the complex interplay of topographic factors shaping sediment distribution. Bed load transport rates vary across sediment roundness and river reach types, with round particles exhibiting higher rates and riffles displaying greater transport than pools. Regression analysis confirms the significant influence of river velocity and bed slope on transport rates, emphasizing the importance of hydraulic factors in sediment transport processes. The output from HEC-RAS revealed the highest sediment concentration in this valley during the late summer months directly aligning with the higher flow in these seasons. During these years, critical bed changes in some of the cross-sections were also observed. RS 12521 has witnessed the highest deposition rate of about 2.5 meters and similarly, RS 7006 has witnessed the highest erosion rate of about 2.3 meters. Likewise, the profile plot of the river reveals a series of erosion and deposition processes during this time window, affecting the riverbed and consequently channel morphology.